ECONOMIES OF THE INTERNET II: AFFECT - Baym, Nancy; Paasonen, Susanna; Mowlabocus, Sharif; Wittkower, D.E. (AoIR Selected Papers of Internet Research, 2015)
The internet has increasingly been conceptualized as a space of economic activity. This contemporary imaginary has been particularly influenced by insights from the school of Autonomist Marxism in the foundational work of Tiziana Terranova and through the dominance of Christian Fuchs’ application of Marxist economic concepts. While this has generated great insight into the political economy of the internet, and in particular allowed for the conceptualization of user activity as labor, this approach is only one paradigm for considering the economic activities and implications of the internet. For internet research, there is also the need to move beyond the long schism between political economy and cultural studies as we try to understand user activity that is socially and affectively rich, but emerges from commercial contexts. This series of panels proposes to expand the exploration of the internet as an economic construct in a number of directions. It pluralizes the definition of “economy”, expanding it from the strictly fiscal to include other economies such as the moral, (sub-) cultural, affective, queer, or libidinal (to name merely a few). Various papers propose different economic models for understanding the interactions within and between these various economies. They also expand the range of actors and economic contexts associated with the internet, drawing attention to the intersections of race and gender in particular. The goal of these papers across the various sessions is to expand our imaginary of the internet economy. The generation of affective intensities is arguably central to the internet economy and a key source of value. Social media relies on the interactions between users and the investment in those interactions to generate consumer lock-in and facilitate the on-going contribution of taste-identifying data that is appropriated and sold to internet advertisers and marketers. However, the value generated by these exchanges cannot be reduced to only the monetary. The labor of users and the products this work generates also circulate in other economies, where value is socially embedded and which refuse the formal alienation associated with the fiscal. The studies in this panel engage with these other economies, investigating their internal dynamics and the socially meaningful mechanisms by which resources are produced, distributed and valued in digital media. The first speaker begins with an exploration of personal and intimate connections in social media, offering musicians as the exemplification of the contemporary trend towards self-branding in the way they use online relationships with fans as a professional strategy. This paper explores this demand to connect with audiences as a form of work, specifically as “relational labor”. Drawing on interview data exploring how musicians understand their relationship with their audiences, the speaker explains this concept, emphasizing the ongoing communicative practices and skills required to sustain this affectively rich economy. Continuing the focus on the processes through which affective states become valued, the second speaker engages with virtual content distributor Distractify, conceiving it as more than a site exploiting the audience commodity. Instead, the speaker notes the entanglement of distraction, attention and affect in its model of value production. Conceptualizing the cognitive and affective work involved in the user experience, the speaker argues for a move from investigating a binary between distraction and attention towards investigation of the rhythms and tempos of user engagement in order to understand this economy. The third speaker also focuses on the dynamics of distraction and attention but this time in the use of smartphones. Combining psychoanalytic methods and political economy approaches, this speaker identifies the phone as a transitional object integral to the negotiations between Self and Other. The centrality of our relationships to the smartphone and the individuation enacted there is then linked to a culture of narcissism emerging from conditions of political, social, economic and environmental precarity. In this speaker’s argument, the distracted use of the smartphone is of value individually and socially, providing a bulwark against the insecurities of the contemporary context. The final speaker also explores the valorization and distribution of quotidian information exchanges on the internet, offering a postphenomological analysis shaped by feminist ethics of care. The speaker describes the moral intuitions that we attach to asymmetrical information flows, offering a theoretical account of what it is to be a “lurker” or a “creeper,” and of how these commonly-used terms of disapprobation do indeed meaningfully identify common ways of failing to act in an appropriate and caring fashion in the conduct of personal relationships online. The argument is then extended to a variety of case studies including targeted advertising, the right to be forgotten, predictive services, and brand-user interactions, to explore how the ethics of care can also help us better understand the significance of asymmetrical information exchanges in internet economies.